Deletion in 1p36.33-p36.32 is associated with pancytopenia: a case report - Huanhuan Yang; Jun Huang; Hao Zheng; Yunfan Zhang; Yuanzhen Zhang; Wei Liu; Jinrong Wu; Xiaobin Chen; Jinfeng Lin; Yanna Ni; Xiaojing Nie (BMC, 2023)
Abstract Background 1P36 deletion syndrome is recognized as the most common terminal microdeletion syndrome in humans, characterized by early developmental delay and consequent intellectual disability, seizure disorder, and distinctive facial features. Variable deletion locations may attributed to phenotypic variability. However, the abnormal phenotypes of hematology are rarely reported in 1P36 deletion syndrome patients. Case presentation We present a case of postnatal intellectual disability accompanied by pancytopenia. Copy number variation analysis revealed a pathogenic deletion in 1p36.331p36.32 with a deletion size of 2.21 Mb. Following successful treatment with glucocorticoids, the patient was diagnosed with immuno-related hemocytopenia (IRH). Discussion The patient experienced IRH, an uncommon characteristic of 1p36 deletion syndrome. The deletion fragment of 1p36.33-p36.32, particularly the loss of GNB1 gene, has been associated with the development of pancytopenia. Genotype-phenotype correlations are valuable in identifying the genes responsible for various clinical characteristics of the syndrome by associating phenotypic variation with specific genes located within the chromosome deletion region. Genome sequencing is recommended in cases where clinical manifestations indicate the presence of a genetic disorder but pose diagnostic challenges.